2011
DOI: 10.1158/0008-5472.can-10-2868
|View full text |Cite|
|
Sign up to set email alerts
|

LOXL2-Mediated Matrix Remodeling in Metastasis and Mammary Gland Involution

Abstract: More than 90% of cancer patient mortality is attributed to metastasis. In this study, we investigated a role for the lysyl oxidase-related enzyme lysyl oxidase-like 2 (LOXL2) in breast cancer metastasis, in both patient samples and in vivo models. Analysis of a published microarray data set revealed that LOXL2 expression is correlated with metastasis and decreased survival in patients with aggressive breast cancer. In immunocompetent or immunocompromised orthotopic and transgenic breast cancer models we showed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
240
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 230 publications
(266 citation statements)
references
References 43 publications
19
240
0
1
Order By: Relevance
“…We have previously shown that inhibiting LOXL2 in mammary cancer cells reduces tumor cell invasion and metastasis without reducing primary tumor growth (24). The data we have presented here suggest that the decreased metastasis observed following LOXL2 inhibition is due not only to decreased invasion of the tumor cells themselves but also to reduced fibroblast activation in the tumor stroma.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…We have previously shown that inhibiting LOXL2 in mammary cancer cells reduces tumor cell invasion and metastasis without reducing primary tumor growth (24). The data we have presented here suggest that the decreased metastasis observed following LOXL2 inhibition is due not only to decreased invasion of the tumor cells themselves but also to reduced fibroblast activation in the tumor stroma.…”
Section: Discussionsupporting
confidence: 50%
“…4T1 cells were infected with a scrambled control or mouse LOXL2-specific shRNA viruses to generate knockdown (4T1 shLOXL2) and control (4T1 control) cell lines. The shLOXL2 cell lines had significantly decreased expression of LOXL2 mRNA and protein compared with controls (24). ELISA and activity assays were conducted to further confirm that shLOXL2 cells expressed less LOXL2 protein and had lower LOXL2 activity (Supplementary Fig.…”
Section: Inhibition Of Loxl2 Reduces A-sma Expression In 4t1 Orthotopmentioning
confidence: 97%
See 3 more Smart Citations